DAMPAK COVID-19 TERHADAP KINERJA KEUANGAN DAERAH (Studi Kasus Pada 34 Pemerintah Provinsi di Indonesia) - Fitri Rahmawati; Endang Kiswara (Diponegoro Journal of Accounting, 2022)
This study aims to determine the Impact of the Covid-19 Pandemic on Regional Financial Performance of Provincial Governments in Indonesia. In addition, this study aims to determine whether there are differences in the regional financial performance of provincial governments in Indonesia during Covid-19 compared to before Covid-19. This study is a replication of the research conducted by Vladimir, et al (2020) in Russia. This study looks at the financial aspects of the APBD realization report, but the proxy measurement variables used are different. The sample population in this study were 34 provinces. This study uses secondary data sourced from the APBD Realization Report (Regional Revenue and Expenditure Budget) from 2019 to 2020. The test tool used is parametric using Paired T-Test. Based on the results of the study, this study states that the ratio of financial performance to the effectiveness of PAD, the ratio of regional tax contributions to PAD, and the ratio of capital expenditures have significant differences before and during the Covid-19 pandemic. The ratio of the degree of fiscal decentralization, the ratio of financial independence, and the ratio of regional retribution contributions did not experience significant differences before and during Covid-19.